Novel Design For Electrical Fan - Noraishah A Razak,, Noraishah (2010)
The ceiling fan uses an electrical motor but this motor is not fully used. The idea of this project is to utilize the ceiling fan’s electrical motor so that it can operate as a normal ceiling fan and at the same time generate a power supply to other loads. Therefore, the aim of this project is to produce the novel design of electrical machine which can operate as motor and generator at the same time.